Leptin Receptor-Deficient db/db Mice Show Significant Heterogeneity in Response to High Non-heme Iron Diet - Paeschke, Sabine; Winter, Karsten; Bechmann, Ingo; Klöting, Nora; Blüher, Matthias; Baum, Petra; Kosacka, Joanna; Nowicki, Marcin (Frontiers in Nutrition, 2021)
Recent studies have shown an association between iron homeostasis, obesity and diabetes. In this work, we investigated the differences in the metabolic status and inflammation in liver, pancreas and visceral adipose tissue of leptin receptor-deficient db/db mice dependent on high iron concentration diet. 3-month-old male BKS-Leprdb/db/JOrlRj (db/db) mice were divided into two groups, which were fed with different diets containing high iron (29 g/kg, n=57) or standard iron (0.178 g/kg; n=42) concentrations for 4 months. As anticipated, standard iron-fed db/db mice developed obesity and diabetes. However, high iron-fed mice exhibited a wide heterogeneity. By dividing into two subgroups at the diabetes level, non-diabetic subgroup 1 (< 13.5 mmol/l, n=30) significantly differed from diabetic subgroup 2 (> 13.5 mmol/l, n=27). Blood glucose concentration, HbA1c value, inflammation markers interleukin 6 and tumor necrosis factor α and hem oxygenase 1 in visceral adipose tissue were reduced in subgroup 1 compared to subgroup 2. In contrast, body weight, C-peptide, serum insulin and serum iron concentrations, pancreatic islet and signal ratio as well as cholesterol, LDL and HDL levels were enhanced in subgroup 1. While these significant differences require further studies and explanation, our results might also explain the often-contradictory results of the metabolic studies with db/db mice.